Kelimpahan Thrips parvispinus Karny dan Musuh Alaminya pada Tanaman Cabai Rawit (Capsicum frutescens L.) - Sumaradana, I Gede; Wijaya, I Nyoman; Adnyana, I Made Mega (Nandur, 2021)
This aims of the research is to search the abudance of T. parvispinus Karny and its natural enemies on Cayenne Pepper ( Capsicum frutescens .L). The research started from November 2020 to January 2021 at Melinggih Kelod Village, Payangan District, Gianyar Regency and at the Plant Pest Laboratory, Faculty of Agriculture, Udayana University. The study was conducted using a descriptive method by conducting a diagonal survey of 20 samples of cayenne pepper that were attacked by T. parvispinus . Observations were made by observing 10 leaves and 10 flowers of cayenne pepper plants. The results showed that the abundance of T. parvispinus in the vegetative and generative phases fluctuated where the highest population of T. parvispinus occurred in plants aged 10 week after transplanting with an average population of 15.8 individuals per plant then decreased in plants aged 11 WAT with an average population 9.75 individuals. The results showed that there were two types of predators that preyed on T. parvisvinus , namely Chrysoperla carnea with an average population of 23.3 and Coccinela transversalis with an average of 22.4 individuals. Laboratory reseach showed that the type of parasitoid that emerged from the 100 nymphs that were caught was Ceranisus spp with an average population of 10.2 individuals.